Рассказы о войне - Алексеев Сергей Петрович (Школьная библиотека, 2019)
Экземпляры: ДБ (20210630) / Инвентарный номер: 53920 / Цена: 168.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 47 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6